Análisis del sistema de intermediación de financiera confianza, del departamento de Loreto, periodo 2017 - 2021 - Ruiz Melendez, Manases (2023)
The objective is to characterize the financial intermediation system of Financiera Confianza, of the Department of Loreto, period 2017-2021. The type of research is descriptive level and quantitative approach, with non-experimental research design, simple descriptive longitudinal cut. The population is finite, statistical registration on the web portal of the Superintendency of Banking and Insurance, non-probabilistic sampling of the intentional type. The technique was documentary analysis, and the instrument was content analysis. The result of the first dimension is that the annual growth rate of deposits is 25%, being an erratic or mobile behavior, with its lowest peak of 2% in 2021 and the highest of 114% in 2018, the second dimension concludes that the annual growth rate of credits is 2%, being an erratic or mobile behavior, with its lowest peak of -14% in 2021 and the highest of 20% in 2019, and the last dimension, it is concluded that the annual participation rate of deposits has an ascending linear behavior, its highest peak being 0.04% in 2021 and the lowest of 0.02% in 2017. The annual participation rate of placements has a linear stable behavior, its peak being lower high of 0.09% in 2021 and the lowest of 0.08% in 2018. We conclude that the average financial intermediation ratio is 23%, that is, the deposits captured represent 23% of the loans granted, with a financing deficit.